Design and characterization of a dust dispenser for tungsten dust injection experiments in the STOR-M tokamak. Issue 1 (1st February 2022) - Nelson, N.; Couëdel, L.; Xiao, C.
Abstract : A dust dispenser has been designed and characterized for future experiments in the STOR-M tokamak. Controlled dust injection is demonstrated in a test-bench device and characterized with different techniques. Upon activation of the dispenser, a plume of dust particles is dispensed. The particle size distribution is found using scanning electron emission images. A laser is used to illuminate the falling particles dispensed and a fast video camera is used to track the images of those particles. The evolution of the spatial distribution of the falling particles is reconstructed using those images based on a free-fall model. The total mass of the dispensed dust particles is directly measured using an analytic balance and is also inferred from the intensity of the scattered light recorded by the video camera.